Construction and evaluation of a combined model of NAA/STZ-induced type 2 diabetes with carotid balloon injury in SD rats - Wang, Yanmei; Zhou, Qian; Li, Chengshan; Chenmou, Xiaojing; Zhu, Chan; Chen, Qiu (Frontiers in Endocrinology, 2025)
PurposeDiabetic macroangiopathy is a leading cause of disability and mortality in type 2 diabetes mellitus (T2DM) patients, but existing animal models have limitations such as complex genetic manipulation or long induction cycles. This study constructed and evaluated a combined model of nicotinamide (NAA)/streptozotocin (STZ)-induced T2DM and carotid balloon injury in Sprague–Dawley (SD) rats.MethodsSixty male SD rats were divided into four groups: control, VBI (only vascular balloon injury), T2DM (only NAA/STZ-induced T2DM), and T2DM+VBI (combined model) groups. T2DM was induced via NAA (110 mg/kg) followed by STZ (65 mg/kg); VBI was performed via a percutaneous transluminal coronary angioplasty (PTCA) balloon catheter. Over 6 weeks, metabolic indicators [intake, excretion, body weight, and random blood glucose (RBG)] were monitored; carotid tissues were collected at 2, 4, and 6 weeks post-VBI for HE staining and immunohistochemistry (α-SMA, F4/80, and MMP-9); and blood cell counts and plasma biochemistry were analyzed.ResultsThe T2DM induction success rate was 90% (no mortality); the postoperative mortality rate was 14.3% in the T2DM+VBI group (vs. 7% in the VBI group). The T2DM and T2DM+VBI groups presented typical diabetic symptoms and persistent hyperglycemia. Histologically, only the VBI and T2DM+VBI groups exhibited time-dependent neointimal proliferation, with T2DM+VBI exhibiting a larger neointimal area, a greater proliferation index, more severe luminal stenosis (2-week hyperplasia comparable to VBI 6 weeks) and increased F4/80-positive macrophages/MMP-9 (poor plaque stability). No major organ abnormalities (except T2DM hepatic steatosis) or intergroup blood parameter differences were found.ConclusionThis combined model has stable hyperglycemia, obvious neointimal hyperplasia, rapid modeling and a high success rate (optimal observation window: 2–4 weeks post-VBI). It recapitulates diabetic macroangiopathy pathology and is suitable for investigating therapeutic efficacy and related molecular/cellular mechanisms.